Thriving in academic leadership - Ferris, Sharmila Pixy; Waldron, Kathleen (Emerald Publishing Limited, 2023)
Demands on institutions of higher education are constantly growing, and recent years, including the Coronavirus pandemic, have complicated academic life in unprecedented ways. The impact of complex and dynamic outside forces, from the pandemic to the interacting socio-cultural, political, economic, and technological factors, calls for strengthened leadership. Yet the 21st century has seen reduced participation by faculty in leadership roles, even though the numbers of faculty globally are rising. Better support is needed to encourage and inspire early and mid-career scholars in pursuing leadership. Thriving in Academic Leadership provides just that, presenting informative and inspiring stories from academic leaders at colleges and universities across the world, including Australia, Canada, India, Ireland, New Zealand, Singapore, South Africa, the United Kingdom and the United States. Personal and engaging, the stories speak to a broad population of academics, serving as an inspiration and guide for academics who aspire to leadership, or are currently in leadership positions, looking to climb the leadership ladder.
Keywords: Educational leadership.; Education, Higher -- Administration.; Education -- Leadership.; Organization & management of education.; elektronické knihy; electronic books